2022
DOI: 10.7717/peerj.13157
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and quantification of Tilapia tilapinevirus from water using a simple iron flocculation coupled with probe-based RT-qPCR

Abstract: Background Tilapia tilapinevirus, also known as tilapia lake virus (TiLV), is a significant virus that is responsible for the die-off of farmed tilapia across the globe. The detection and quantification of the virus using environmental RNA (eRNA) from pond water samples represents a potentially non-invasive and routine strategy for monitoring pathogens and early disease forecasting in aquaculture systems. Methods Here, we report a simple iron flocculation method for concentrating viruses in water, together w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…RT-qPCR or qPCR procedures have been developed and optimized for the detection and quantification of viral or bacterial loads in infected tilapia. Target pathogens include TiLV, 55,56,88 ISKNV, 89 TiPV, 74 S. agalactiae 64,90 and F. orientalis. [91][92][93] Several multiplex TaqMan qPCR assays have also been developed to detect and quantify three to four pathogen species in a single PCR test, such as F. orientalis, S. iniae and S. agalactiae 94 ; A. hydrophila, A. veronii and A. schubertii 95 ; and E. ictaluri, E. tarda, E. anguillarum and E. piscicida.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
See 3 more Smart Citations
“…RT-qPCR or qPCR procedures have been developed and optimized for the detection and quantification of viral or bacterial loads in infected tilapia. Target pathogens include TiLV, 55,56,88 ISKNV, 89 TiPV, 74 S. agalactiae 64,90 and F. orientalis. [91][92][93] Several multiplex TaqMan qPCR assays have also been developed to detect and quantify three to four pathogen species in a single PCR test, such as F. orientalis, S. iniae and S. agalactiae 94 ; A. hydrophila, A. veronii and A. schubertii 95 ; and E. ictaluri, E. tarda, E. anguillarum and E. piscicida.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…191,200 The application of eDNA/eRNA for tilapia disease diagnosis is still limited, however, a straightforward approach for TiLV detection and quantification from water that employed a simple iron flocculation method for viral concentration coupled with a probe-based RT-qPCR has been described. 55 TiLV nucleic acid was detected and quantified in water collected from affected ponds/cages as well as sewage, and a reservoir. This approach might be effective for noninvasive monitoring of TiLV in aquaculture environments, and allow suitable biosecurity interventions.…”
Section: Environmental Dna and Rna For Early Detection Of Pathogens F...mentioning
confidence: 99%
See 2 more Smart Citations
“…There are mainly two different forms of virus that infect fish species which are either DNA virus or the RNA virus. Several studies have shown that DNA and RNA from virus can be detected using eDNA or eRNA method (Minamoto et al 2009;Haramoto et al 2007;Kawato et al 2021;Taengphu et al 2021;Vilaca et al 2020;Miaud et al 2019;Weli et al 2021;Bernhardt et al 2020). Since DNA is more stable than RNA, detection of eDNA is more practical and easier than detecting RNA from an environmental source.…”
Section: Virusmentioning
confidence: 99%